Reinterpreting the Highest Formula of Affirmation - Chen, Junze (Dianoia: The Undergraduate Philosophy Journal of Boston College, 2026)
Nietzsche develops different approaches to the problem of eternal recurrence throughout his works. This disunity in Nietzsche’s presentation of the doctrine led some interpreters to argue that there are two inherently incompatible notions of eternal recurrence — one ethical and one cosmological — which mark a change in Nietzsche’s idea between his middle and later work. Different from these interpreters, I argue that the two notions of eternal recurrence already coexist in Part III of Thus Spoke Zarathustra. In “The Vision and the Riddle,” Nietzsche already presented the problem of eternal recurrence as a contradiction between moment and eternity within the framework of linear temporality. Since the riddle of eternal recurrence concerns the contradiction between two terms, I propose that the riddle inherently opens to two possible solutions: one that focuses on the moment (the ethical eternal recurrence) and one that focuses on eternity (the cosmological eternal recurrence). These two solutions to the riddle, further developed by Nietzsche in “The Convalescent,” become two opposing ways of formulating the doctrine of eternal recurrence. I will eventually relate the two formulas of eternal recurrence to Nietzsche’s project of overcoming nihilism. I argue that Nietzsche ultimately privileges the ethical formula of eternal recurrence above the cosmological formula. The thinking of eternal recurrence concerns not simply the factuality of the doctrine, but also whether the thinker has the power to endure its consequence. Nietzsche’s philosophy overcomes nihilism not because it replaces nihilism with a more refined metaphysics of will to power, but rather because it demands that thinkers unconditionally affirm the consequences of their theory. This demand for ethical self-affirmation prevents Nietzsche’s philosophy from becoming, in Heidegger’s words, a “fulfillment of nihilism proper.”